Pengaruh Upah Minimum, Telepon Seluler, dan Pengawasan Ketenagakerjaan terhadap Kewirausahaan dan Produktivitas Tenaga Kerja di Indonesia Tahun 2022 - Sabillah, Hanif; Prasetyo, Rokhmirati; Sepbrina Br Lumban Gaol, Ruth Natasya; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2024)
Entrepreneurship and labor productivity in Indonesia still face challenges. According to The Asian Productivity Organization (APO) Productivity Databook 2022, labor productivity per capita in Indonesia is lower compared to other ASEAN countries. This study aimed to provide a general overview of minimum wage factors, mobile phone, and labor inspection, as well as determine the influence of these factors on entrepreneurship and labor productivity in Indonesia in 2022. The data used includes the 2022 the Digital Competitiveness Index (EV-DCI) reports from East Ventures, data from the Indonesian Ministry of Manpower, and data from Badan Pusat Statistik (BPS). The research method employed descriptive analysis and inferential analysis. Inferential analysis used multiple linear regression with the Ordinary Least Squares (OSL) method. Every 1% increase in the number of labor supervisors will increase entrepreneurship and productivity by 0.161%. Meanwhile, the minimum wage will decrease entrepreneurship and productivity by 0.831%. Otherwise, the percentage of households with cellular phones will increase entrepreneurship and productivity by 4.556%.